LINGUISTIC REALIZATIONS OF THE ABSTRACTS IN INFORMATICS, COMPUTER SCIENCE & ENGINEERING, AND INFORMATION SYSTEMS JOURNALS - Nurhayati S.; Fadilah Fadilah (Universitas Nasional, 2023)
The abstract is now a required part of a Research Article (RA) for most scientific publications. It is recognized that the functions, linguistic realizations, and rhetorical structures of abstracts and RAs vary (Lores 2004). The study aims to examine how each step in RA abstracts is expressed linguistically. The data come from 30 RA abstracts taken from two Informatics, Computer Science & Engineering, and Information Systems in COMMIT (Communication and Information Technology) Journal and Khazanah Informatika, Jurnal Ilmu Komputer dan Informatika published in 2021-2022. According to Hyland's theory, the writers enumerated each move frequency of the rhetorical structure: Introduction (M1), Purpose (M2), Method (M3), Results (M4), and Conclusion (M5). The writers then examined each move's linguistic realizations, paying particular attention to the word tense and lexis. It was discovered that the category of